Pharmacological Strategies to Retard Cardiovascular Aging. Issue 10 (13th May 2016) - Alfaras, Irene; Di Germanio, Clara; Bernier, Michel; Csiszar, Anna; Ungvari, Zoltan; Lakatta, Edward G.; de Cabo, Rafael
Abstract : Aging is the major risk factor for cardiovascular diseases, which are the leading cause of death in the United States. Traditionally, the effort to prevent cardiovascular disease has been focused on addressing the conventional risk factors, including hypertension, hyperglycemia, hypercholesterolemia, and high circulating levels of triglycerides. However, recent preclinical studies have identified new approaches to combat cardiovascular disease. Calorie restriction has been reproducibly shown to prolong lifespan in various experimental model animals. This has led to the development of calorie restriction mimetics and other pharmacological interventions capable to delay age-related diseases. In this review, we will address the mechanistic effects of aging per se on the cardiovascular system and focus on the prolongevity benefits of various therapeutic strategies that support cardiovascular health.